2019
DOI: 10.1002/jia2.25411
|View full text |Cite
|
Sign up to set email alerts
|

HIV pretreatment drug resistance among cisgender MSM and transgender women from Lima, Peru

Abstract: Introduction Transmitted, or any pretreatment drug resistance (TDR, PDR) can compromise efficacy of first‐line antiretroviral therapy (ART). In Peru, genotypic resistance testing is not routinely performed before ART initiation, and estimated PDR prevalence prior to 2012 ranged from 1.0% to 4.7%. We aimed to update estimates of PDR prevalence in men who have sex with men (cis‐MSM) and transgender women (TW). Methods We obtained HIV sequences from three studies of ART‐naïve cisgender‐MSM and TW (n = 470) in Lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
2
10
2
3
Order By: Relevance
“…Azidothymidine (AZT), lamivudine (3TC), and tenofovir (TDF), as rst-line NRTI drugs in China, have meager rates of transmission resistance (0.3%, 0.15%, and 0%, respectively). However, unlike the ndings reported in other studies, [4,5,[36][37][38][39][40] NRTI resistance showed the most signi cant increase (from 0% to 5.17%) from 2009 to 2017 in this study. Although the prevalence of TDR to PIs (0.44%) was signi cantly lower than the prevalence of TDR to NNRTIs/NRTIs, the I54M mutation caused universal resistance to PI drugs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Azidothymidine (AZT), lamivudine (3TC), and tenofovir (TDF), as rst-line NRTI drugs in China, have meager rates of transmission resistance (0.3%, 0.15%, and 0%, respectively). However, unlike the ndings reported in other studies, [4,5,[36][37][38][39][40] NRTI resistance showed the most signi cant increase (from 0% to 5.17%) from 2009 to 2017 in this study. Although the prevalence of TDR to PIs (0.44%) was signi cantly lower than the prevalence of TDR to NNRTIs/NRTIs, the I54M mutation caused universal resistance to PI drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…[3] TDR has been detected in ART-naïve populations in the United States, Switzerland, Peru, Argentina, Brazil, and Colombia, and the estimate of the number of people infected with virus carrying TDR mutations has increased with time. [3][4][5] In these populations, demographic and clinical characteristics usually cannot predict TDR. Interestingly, some studies reported higher CD4 counts in people with TDR mutations (TDRMs) than in individuals without TDRMs, [6,7] but others came to the opposite conclusion.…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…The study showed that the prevalence of transgender and gender non-conforming identifying MSM accounted for 8.8% of the total population. A previous study reported that 23% of sample were identi ed as gender minorities among the MSM population [5], while yet another study found that 9% of the MSM population were identi ed as transgender women [19]. This existing discrepancies among different studies could be attributed to various assessment tools of gender identify, different districts, and cultural norms, etc.…”
Section: Discussionmentioning
confidence: 97%
“…In recent studies, there has been a call for further analysis of gender identity among men who have sex with men (MSM) for HIV interventions around the world [3,4]. Previous international studies have shown that transgender and gender non-conforming MSM account for over 23% of the MSM population [5]. In Jobson's survey of one city of South African, it was also reported that 9% of individuals identi ed as gender minorities among the MSM population [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies around the world, there has been a call for further analysis of HIV interventions that target different gender identities among men who have sex with men (MSM) [3][4][5]. Previous research has shown that transgender and gender non-conforming MSM account for over 23% of the MSM population in Peru [6]. Jobson et al found that 9% of individuals were identi ed as gender minorities within the MSM population in a city of South Africa [7].…”
Section: Introductionmentioning
confidence: 99%